Nutritional quality analysis of different Moringa provenance in Bale, Southeast Ethiopia - Mengistu, Bikila; Soboka, Shure (International Journal of Agricultural Research, Innovation and Technology, 2023)
Moringa is a tree with medicinal, nutritional, industrial, and socio-economic values. Moringa leaf extracts have potential antihypertensive, antispasmodic, antiulcer, diuretic, hepato-protective and cholesterol-lowering activities. The study was conducted to analyze the nutritional quality of different moringa provenances and to promote the best provenances for the end users. Field experiments were conducted in Goro and Dallo Mena districts of Bale located in Oromia regional state of Ethiopia. Collected samples were air-dried at room temperature and milled for laboratory analysis. According to this study growing environment did not bring significant variation (P>0.05) in average mineral contents like Mg, Zn, P and CP content of the provenances. But significantly higher (P<0.05) Na, K, and Ca were recorded for the samples collected from Dallo Mena district, whereas higher Ash and Fe content was recorded in Goro district. On the other hand, provenance from Dallo Mena and Bako is superior to most of the quality characters analyzed. However, the one from Arbaminch is higher in Na and Zn contents. Provenance from Abay Filiklik is higher in Ash, K and P content. Moringa leaf is rich in Ash, Zn, Cp, and Mg to the sufficient level, while Fe, Ca and P are to the level of high or double to triple to the optimum level when compared to the optimum nutrient content of plant material. Generally, higher mean and individual chemical quality values were recorded from provenances grown in Dallo Mena district except for K, Fe, Zn, and CP, which are higher in Goro. Int. J. Agril. Res. Innov. Tech. 13(1): 83-88, June 2023